Flexible and Binder‐Free Organic Cathode for High‐Performance Lithium‐Ion Batteries. (11th March 2014) - Wu, Haiping; Shevlin, Stephen A.; Meng, Qinghai; Guo, Wei; Meng, Yuena; Lu, Kun; Wei, Zhixiang; Guo, Zhengxiao
<x xml:space="preserve">Abstract</x> Fabrication of a flexible organic electrode by growing polyimide nanoflakes on single‐wall carbon nanotube films is presented. The flexible electrode exhibits high capacity and outstanding rate capability. This electrode is promising for the application in high‐power flexible lithium‐Ion batteries. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>